2007
DOI: 10.1002/eji.200737621
|View full text |Cite
|
Sign up to set email alerts
|

Activation of retinoic acid receptor‐α favours regulatory T cell induction at the expense of IL‐17‐secreting T helper cell differentiation

Abstract: Autoimmunity is thought to reflect an imbalance between regulatory T helper lymphocytes (Treg) and pathogenic, IL-17-secreting T helper (Th17) cells. Induction of both adaptive Treg and Th17 cells requires signalling from TGF-b. We now show that, in the context of TGF-b signalling, all-trans retinoic acid (ATRA) leads to increased induction of CD4 + T cells expressing the Treg specification factor forkhead box protein P3 (FoxP3) and decreased frequency of cells expressing IL-17, even in the presence of IL-6. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
167
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(178 citation statements)
references
References 20 publications
9
167
1
1
Order By: Relevance
“…Several studies have demonstrated that RA can negatively affect the differentiation of T H 17 cells [26][27][28][29] although the precise mechanisms remain unclear. Based on our data showing heightened IL-17A production by HIC1-deficeint T H 17 cells in vitro and in vivo, we hypothesized that expression of HIC1 would be required for the RA-dependent reduction in T H 17-cell differentiation.…”
Section: Hic1 Is Not Required For Inhibitory Effects Of Ra On T H 17-mentioning
confidence: 99%
“…Several studies have demonstrated that RA can negatively affect the differentiation of T H 17 cells [26][27][28][29] although the precise mechanisms remain unclear. Based on our data showing heightened IL-17A production by HIC1-deficeint T H 17 cells in vitro and in vivo, we hypothesized that expression of HIC1 would be required for the RA-dependent reduction in T H 17-cell differentiation.…”
Section: Hic1 Is Not Required For Inhibitory Effects Of Ra On T H 17-mentioning
confidence: 99%
“…22 The effect of atRA on Treg and Th17 cells is dependent upon the RA receptor/retinoid X receptor heterodimer. 49,50 Because the pathogenesis and development of many autoimmune diseases is affected by the imbalance between Treg and Th17 cells, the role of atRA in regulating this balance may greatly affect the progress of autoimmune diseases.…”
Section: Foxp3 and Treg Cell Subsetsmentioning
confidence: 99%
“…85 In development, endogenous ATRA is required for homeostasis in the immune system and for gut homing of T lymphocytes and their increased expression of Foxp3. As ATRA promotes the Treg lineage, 81,82,84,[86][87][88] it is worth asking, is there any evidence for cross-regulation between ATRA and LIF? Importantly, LIF influences oxidative conversion of vitamin A to ATRA in mouse embryonic stem cell; 89 also, LIF synergises with ATRA in differentiation of neural precursor cells to astrocytes 90 and ATRA induces LIF expression in oligodendrocytes: 91 furthermore LIF is induced by ATRA in mouse embryonic stem cell.…”
Section: Lif As a Therapy For Msmentioning
confidence: 99%